2000
DOI: 10.1002/(sici)1096-9845(200002)29:2<241::aid-eqe903>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Control design for seismically excited buildings: sensor and actuator reliability

Abstract: SUMMARYIn this paper we present control design methods that provide desirable levels of performance and simultaneously account for actuator and sensor reliability (or malfunction) for buildings under seismic excitations. Performance is de"ned in terms of the disturbance attenuation (i.e.¸ gain) from the disturbances to the controlled outputs of the system. The reliability of actuators and sensors refers to the deviation of actual control forces or actual sensor measurements from their ideal levels. Simulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Moreover, the use of the disturbance observer can be found in the control scheme of Nyawako et al (2016). Alt et al (2000) reported that, during an earthquake, the measured signals from the sensors may deviate from the real ones and this could result to a detrimental effect on the controlled structure.…”
Section: Software-related Limitationsmentioning
confidence: 99%
“…Moreover, the use of the disturbance observer can be found in the control scheme of Nyawako et al (2016). Alt et al (2000) reported that, during an earthquake, the measured signals from the sensors may deviate from the real ones and this could result to a detrimental effect on the controlled structure.…”
Section: Software-related Limitationsmentioning
confidence: 99%
“…The lower subsystem is composed of floors 1-12, while the upper subsystem is composed of floors [8][9][10][11][12][13][14][15][16][17][18][19][20]. The overlapping appears in the part of the columns between the 8th and the 12th floors.…”
Section: The Approach For Solving the Problemmentioning
confidence: 99%
“…[ 44,45 ] Additionally, it is often that the actuators installed on structures are only periodically inspected/calibrated leading to poor performance. [ 46 ] The actuator uncertainty could be associated with instability and poor control performance [ 44,45 ] thus, it is crucial to also consider its effect within the simulation process.…”
Section: Introductionmentioning
confidence: 99%
“…[44,45] Additionally, it is often that the actuators installed on structures are only periodically inspected/calibrated leading to poor performance. [46] The actuator uncertainty could be associated with instability and poor control performance [44,45] thus, it is crucial to also consider its effect within the simulation process. This work is structured as follows: Sections 1.1 and 1.2 include an extended review of studies which dealt with parametric and input uncertainty, respectively.…”
Section: Introductionmentioning
confidence: 99%